2006
DOI: 10.1002/ijc.21558
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and lifestyle determinants of mammographic breast density. A longitudinal study in a Mediterranean population

Abstract: High mammographic breast density (H‐MBD) has been associated with increased breast cancer (BC) risk, even after adjustment for established BC risk factors. Only a few studies have examined the influence of diet on MBD. In a longitudinal study in Florence, Italy, we identified about 2,000 women with a mammogram taken 5 years after enrollment, when detailed information on dietary and lifestyle habits and anthropometric measurements had been collected. Original mammograms have been identified and retrieved (1,668… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
139
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(155 citation statements)
references
References 41 publications
11
139
5
Order By: Relevance
“…Among food-based analyses conducted in other populations, one study reported a positive association between meat intake and breast density [32]. Another [33] reported an inverse association between vegetable intake and breast density, but two others did not [32,34]. In nutrient-based analyses, several studies reported positive associations for total and saturated fat, protein, and alcohol intake [32,33,[35][36][37][38], and inverse associations for intake of fiber, carotenoids, calcium, and vitamin D [33,35,[39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among food-based analyses conducted in other populations, one study reported a positive association between meat intake and breast density [32]. Another [33] reported an inverse association between vegetable intake and breast density, but two others did not [32,34]. In nutrient-based analyses, several studies reported positive associations for total and saturated fat, protein, and alcohol intake [32,33,[35][36][37][38], and inverse associations for intake of fiber, carotenoids, calcium, and vitamin D [33,35,[39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Another [33] reported an inverse association between vegetable intake and breast density, but two others did not [32,34]. In nutrient-based analyses, several studies reported positive associations for total and saturated fat, protein, and alcohol intake [32,33,[35][36][37][38], and inverse associations for intake of fiber, carotenoids, calcium, and vitamin D [33,35,[39][40][41][42]. The generally inconsistent evidence for an association between diet and mammographic density in previous studies leaves open the possibility that mammographic density may not mediate dietary effects, if any, on breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…34 Currently, the relationship between breastfeeding and mammographic density is a matter of controversy, given that both positive and inverse associations have been found. 32,[35][36][37] The women in our study nursed for a long period (mean of 12.9 years), and their breasts were predominantly non-dense, but despite this, breastfeeding was not significantly associated with mammographic density.…”
Section: -24mentioning
confidence: 99%
“…Randomized control trials demonstrated changes in breast density with intake of low-fat high carbohydrate diet. 70,71 Cross-sectional studies have shown calcium and vitamin D, [72][73][74][75][76] and vegetables 75,77 to be associated with lower breast density.…”
Section: Breast Composition and Radiographic Appearancesmentioning
confidence: 99%
“…It is also increasingly important that screened women with dense breasts are advised to avoid lifestyles such as alcohol intake and exogenous hormone use that have been shown to increase cancer risk in women with dense breast. Also, consumption of food species associated with lower breast density 22,72,75,77 and physical activity 78 is encouraged as these may mitigate their risk of developing breast cancer.…”
Section: Breast Composition and Radiographic Appearancesmentioning
confidence: 99%